2014
DOI: 10.1111/1462-2920.12669
|View full text |Cite
|
Sign up to set email alerts
|

Sioxanthin, a novel glycosylated carotenoid, reveals an unusual subclustered biosynthetic pathway

Abstract: Summary Members of the marine actinomycete genus Salinispora constitutively produce a characteristic orange pigment during vegetative growth. Contrary to the understanding of widespread carotenoid biosynthesis pathways in bacteria, Salinispora carotenoid biosynthesis genes are not confined to a single cluster. Instead, bioinformatic and genetic investigations confirm that four regions of the S. tropica CNB-440 genome, consisting of two gene clusters and two independent genes, contribute to the in vivo producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 58 publications
0
40
0
Order By: Relevance
“…Ps1 and Ps2 strains share two terpene encoding BGCs ( Figures 4B,D , clusters B and D), hydrocarbons comprised of isoprene-derived units that have diverse bioactivities including antimicrobial activity (Gershenzon and Dudareva, 2007; Gallucci et al, 2009). One of these terpene BGCs (cluster B) has similarity to carotenoid BGCs, and encodes a polyprenyl synthetase and a phytoene synthase (Richter et al, 2015), while the other shared terpene BGC (cluster D) contains a terpene cyclase closely related to a lycopene cyclase found in carotenoid biosynthesis. This cluster also has similarity to a conserved cluster in Rhodococcus bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Ps1 and Ps2 strains share two terpene encoding BGCs ( Figures 4B,D , clusters B and D), hydrocarbons comprised of isoprene-derived units that have diverse bioactivities including antimicrobial activity (Gershenzon and Dudareva, 2007; Gallucci et al, 2009). One of these terpene BGCs (cluster B) has similarity to carotenoid BGCs, and encodes a polyprenyl synthetase and a phytoene synthase (Richter et al, 2015), while the other shared terpene BGC (cluster D) contains a terpene cyclase closely related to a lycopene cyclase found in carotenoid biosynthesis. This cluster also has similarity to a conserved cluster in Rhodococcus bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…While this was assumed to be due to carotenoid production, the biosynthetic origin and structures of these compounds had not been defined. A bioinformatic search of the S. tropica strain CNB-440 genome revealed genes associated with carotenoid biosynthesis in four distinct chromosomal regions 123 . Genetic investigations confirmed that, contrary to what is typically observed in bacteria, carotenoid biosynthesis in Salinispora spp.…”
Section: Genome-aided Natural Product Discoverymentioning
confidence: 99%
“…Genome-mining efforts compensate for this deficiency. For example, the production of the glycosylated terpene sioxanthin from Salinispora tropica CNB-400 is dependent on four genetic loci[33], and a single promiscuous enzyme is required for glycosylation during the biosynthesis of a plecomacrolide and methyl-rhamnosylated phenazines in Kitasatospora sp. MBT166[34].…”
Section: Lessons From Chemical Ecologymentioning
confidence: 99%